2022
DOI: 10.1109/lgrs.2020.3034174
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Satellite L-Band Vegetation Optical Depth in the U.S. Corn Belt

Abstract: Satellite L-band vegetation optical depth (L-VOD) contains new information about terrestrial ecosystems. However, it has not been evaluated against the geophysical variable that it represents, plant water, the mass of liquid water contained within vegetation tissue per ground area. We quantitatively assess the seasonal variation of three L-VOD products at the South Fork Core Validation Site in the Corn Belt state of Iowa where L-VOD is directly proportional to crop plant water. We use three satellite-scale cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Simpler one‐dimensional SPAC models have been used to gain insights into plant hydraulic traits and rehydration responses (Feldman, Short Gianotti, et al., 2021; Liu et al., 2021a). Crop models that produce crop water estimates and phenology from meteorological data have also been shown to be useful for validating VOD (Togliatti et al., 2019, 2020).…”
Section: Emerging Validation Methodsmentioning
confidence: 99%
“…Simpler one‐dimensional SPAC models have been used to gain insights into plant hydraulic traits and rehydration responses (Feldman, Short Gianotti, et al., 2021; Liu et al., 2021a). Crop models that produce crop water estimates and phenology from meteorological data have also been shown to be useful for validating VOD (Togliatti et al., 2019, 2020).…”
Section: Emerging Validation Methodsmentioning
confidence: 99%
“…In contrast, there are only few studies reporting how well VOD represents in-situ plant physiology and phenology (e.g., [18]). Studies of how well VOD represents VWC at the satellite scale are becoming more prevalent ( [4], [5], [15], [19]- [21]). These assessments are based on sparse tower measurements and crop models which are highly informative.…”
Section: Introductionmentioning
confidence: 99%
“…In Chapter 3 I have also found that cell measurement may be more representative of the corn canopy, as these are over a longer distance of the filed and measure more plants than radio link systems we have utilized. For verifying satellite remote sensing of cropland vegetation water quantity, the most notable study is by Togliatti et al (2022). Recent validation efforts have also been conducted in northeastern United States forests.…”
Section: Discussionmentioning
confidence: 99%